Gender Parity in Electoral Matters: A Setback Without Alternation in Peru - Arévalo Rengifo, Paola Katherine (2025)
Law No. 32058 on gender parity and alternation in the Peruvian electoral system is analyzed, investigating whether it represents a setback in women's political participation. Focusing on the social construction of gender and the concept of parity as a tool to guarantee an inclusive democracy, it is highlighted that Law No. 31030 made progress in implementing parity and alternation, Law No. 32058 eliminates horizontal parity and alternation in the presidential and regional lists, limiting the obligation to include women in the lists, which reduces the opportunities of access to high level positions for women, affecting female representation. Law No. 32058 implies a setback in gender equality in the Peruvian electoral system, this regulatory change could reduce the effective participation of women in positions of power with negative implications for the consolidation of a parity democracy.